Valores do trabalho no contexto da economia criativa: um estudo com artesãs-empreendedoras da cosmética natural - Silva, Francisco Edson Rodrigues da (2022)
Work values represent what individuals consider important in the work environment, exposing the reasons why individuals work, their alternatives, behaviors and attitudes towards their jobs. Research on this topic can cover various types of occupations and workers, including those referring to the creative economy, which encompasses sectors whose products/services are the result of creativity, talent and local culture. In this scenario, the artisanal natural cosmetics sector brings a production/consumption proposal guided by environmental, social and economic sustainability, highlighting aspects such as the rescue of traditional knowledge, the reduction of waste and the valorization of small artisan productions. Thus, this work aims to analyze how the values of work are manifested among entrepreneurs in the artisanal natural cosmetics sector. The research locus is the city of Fortaleza - CE, approved in 2019 as Creative City, which reinforces the relevance of the study to understand and strengthen the creative business environment in the municipality. Of a qualitative nature, this exploratory-descriptive research carried out a qualitative adaptation of the Revised Scale of Values Relative to Work (EVT-R), by Porto and Pilati (2010), and semi-structured interviews to collect data from seven artisans in the sector. Data analysis was carried out through content analysis, with the help of Atlas.ti software. The results show that the values related to Professional Achievement and Social Relations are the most present, with emphasis on those related to having creative work and collaborating for the development of society. The Prestige and Stability factors were less perceived, but values related to being admired for the work performed and obtaining financial stability are representative. The qualitative adaptation of the EVT-R demonstrated the existence of different meanings for factors of stability and achievement, pointing out the specificities of work values for the artisanal field. The creation of a collaborative network of women in the sector was highlighted and it was revealed that the lack of specific regulation for the activity is the main barrier to the growth of artisans.